Composition and microstructure dependent corrosion behaviour of Mg-Li alloys. (10th January 2018) - Li, C.Q.; Xu, D.K.; Chen, X.-B.; Wang, B.J.; Wu, R.Z.; Han, E.H.; Birbilis, N.
Abstract: The corrosion and electrochemical behaviour of carefully prepared ultra-lightweight magnesium-lithium (Mg-Li) alloys were investigated and compared. The alloy compositions studied were selected to provide the ability to compare unique microstructures and crystal structures, which arise from specific alloying additions of Li. Mg-4%Li is hexagonal closed-packed (HCP) alloy with Li in solid solution of Mg (α-Mg); Mg-14%Li is a fully solid solution BCC (β-Li) alloy, whilst Mg-7.5%Li is a duplex (α-Mg + β-Li) alloy. Testing in 0.1 M NaCl revealed that the corrosion performance and electrochemical response of the Mg-Li system evolved with the composition and crystallographic structure. For Mg-4%Li alloy, filiform-like corrosion morphology can be observed on the corroded surface, whilst a mixture of filiform-like corrosion to the α-Mg and localised dissolution of β-Li existed on the corroded surface of Mg-7.5%Li alloy. In the case of the BCC structured Mg-14%Li alloy, minor pitting was observed, concomitant with a generally low corrosion rate (particularly low corrosion rate for typical Mg alloys) and an increasing corrosion resistance with exposure time were also revealed. A combination of exposure testing inclusive of hydrogen collection and mass loss, in addition to potentiodynamic polarisation and impedance spectroscopy elucidated and quantified the corrosion performance of three differently structured Mg-Li alloys. It revealed that in spite of being composed of reactive elements of Mg and Li, the formation of β-Li phases with BCC structure could facilitate the formation of a highly protective surface film which results in a predictable and consistently low corrosion rate of the Mg-14%Li alloy. Highlights: Corrosion behaviour was dependent on the crystal structure of Mg-Li alloys. Mg-4Li, Mg-7.5Li and Mg-14Li (wt.%) alloys were HCP, HCP + BCC and BCC structure, respectively. Corrosion attack preferentially occurred in α-Mg phase of Mg-7.5Li alloy. Mg-14Li alloy revealed a high corrosion resistance which increased with immersion time. A highly protective surface film could form on Mg-14Li alloy with single β-Li phase.